(untitled) (CAHIERS MAGELLANES-NS, 2024)
The time is focused on existentialism, in particular the work of Albert Camus who is the staunch follower of this movement with the primary emphasis on the idea of the Absurd. It is somewhat different from the principles of existentialism, focusing on such a philosophical vision of the world as the existence of Sartre's existentialism. Thus, Camus insists on the recognition of the absurdity of existence and argues about the kind of rebellion—by which he means to fight against life with all its controversies, not against God and his purpose. This research paper therefore seeks to examine some of Camus' works like; The Myth of Sisyphus, The Stranger, and The Plague to determine his existential themes, its philosophy of individualism, stoicism, and moral morality. It also provides an analysis of the differences that existed between Camus and Sartre on aspects such as freedom and meaning and how the concepts of Camus exist today to explain existential issues. Concerning modern challenges, it is possible to state that Camus' idea of the Absurd Hero, who has to find a sense in the constant fight against the meaninglessness of existence, can be really helpful. Nevertheless, in a world with growing fears and doubts, with people's attempts to find what is genuine, Camus' philosophy is still highly actual, as it explains how people can live in a given world, which is so unpredictable and treacherous.